A structure–activity understanding of the interaction between lignin and various cellulase domains. (May 2022) - Zhao, Xiaoxue; Huang, Caoxing; Lin, Wenqian; Bian, Bin; Lai, Chenhuan; Ling, Zhe; Yong, Qiang
Graphical abstract: Explored the structure–activity relationships of lignin fractions interacted with endo -cellulase and carbohydrate-binding module during enzymatic hydrolysis by non-destructive approaches. Highlights: Fractionation of bamboo kraft lignin (BKL) with different structures. The main forces contribution of BKL to cellulase was emphasized. It provides a new perspective for studying the adsorption mechanism of lignin-enzyme. Abstract: To elucidate the structure–activity relationship between lignin and various cellulase domains, four lignin fractions with specific structures and molecular weight were prepared from bamboo kraft lignin (BKL) and used to investigate the adsorption mechanism between different cellulase domains by fluorescence spectroscopy and SDS-PAGE. Endo-cellulase 6B exhibited a higher affinity to BKL fractions than the carbohydrate-binding module (CBM4A) of cellulase, which is positively correlated to molecular weight. The thermodynamic mechanism showed that the adsorption between BKL fractions and endo -cellulase 6B was dominated by van der Waals and electrostatic forces, while hydrophobic force is the driver for BKL fractions to adsorb CBM4A. Structure-activity relationship between lignin fractions and cellulase domain revealed that thermodynamics and interaction forces were more easily affected by the structure of BKL, including S/G ratio, molecular weight and hydrophobicity. The aforementioned results demonstrated that lignin's structure plays a critical role in its adsorption with various cellulase domains.